"There may not be a rainbow sticker at the door, but there are my rainbow shoes": A qualitative exploration of resilience among LGBTQ+ adults in physical activity contexts. (January 2023) - Herrick, Shannon S.C.; Duncan, Lindsay R.
Abstract: Researchers have identified LGBTQ + -specific stressors that hinder physical activity participation; however, LGBTQ + resilience against these stressors has yet to be explored. The purpose of this study was to gain an understanding of how LGBTQ + resilience is experienced within physical activity. Ten focus groups with LGBTQ + adults ( N = 36) were conducted online and subject to abductive thematic analysis. Experiences of individual resilience were conceptualized through the interplay of: (a) persistence-adaptability (ranging from being regimented with physical activity to being flexible and amenable to changes), (b) toughness-tenderness (possessing mental grit to self-kindness), and (c) complaisance-resistance (internalizing to resisting norms that govern physical activity). Participants also described three sites for community resilience: (a) LGBTQ + communities that provided pivotal social support, but rarely for physical activity, (b) digital communities that could support or thwart LGBTQ + resilience, but often prioritized aesthetics, and (c) physical activity communities that supported participation, but often perpetuated LGBTQ + exclusion. Highlights: Individual and community resilience play an integral role in supporting LGBTQ + participation within physical activity. Self-compassion aligns with aspects of LGBTQ + individual resilience within physical activity (adaptability, tenderness, and resistance). More resources dedicated to fostering LGBTQ + community resilience should be developed and provided within physical activity contexts.